The formation of diamond-like carbon structure anchored in the nitrided layer of M50 steel during plasma-assisted thermochemical treatment. (February 2022) - Yao, Jiawei; Yan, Fuyao; Chen, Hongtao; Chen, Baofeng; Yan, Mufu; Zhang, Yanxiang
Graphical abstract: Highlights: Fabricate self-lubricating gradient composite layer by a straightforward method. The composite layer from DLC gradually transforming to nitrided layer is spontaneously formed during carburizing without adjusting parameters. The gradient structure introduces functionally graded mechanical properties. The layer owns excellent wear resistance and a lower friction coefficient than the nitridied. The nature of self-lubricating effect is graphitization of the tribo-film. Abstract: Diamond-like carbon (DLC) has excellent performance but cannot be directly applied in gears and bearings due to poor adhesion. A novel gradient composite layer that includes a hardened nitrided layer and a self-lubricating DLC structure at the outermost surface was fabricated on M50 steel via plasma-assisted thermochemical treatment. The structure evolution of the modified layer was comprehensively characterized by optical microscopy, scanning electron microscope (SEM), atomic force microscopy (AFM), transmission electron microscope (TEM), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). The results show that the nanoparticles embedded in the DLC structure gradually increase until the nitrided diffusion layer. The DLC structure is like being anchored in the nitrided layer by nanoparticles carbide/nitride. The inner of the pre-nitrided layer is hardly affected during the plasma carburizing process. The gradient structure is verified to endow the treated samples with functionally graded hardness profile and super wear resistance by Vickers hardness tester, Nano-indentation tester, and pin-on-disk tribometer. The composite layer's tribological behavior was discussed through wear scar morphology observation by SEM and chemical structure in tracks with Raman spectroscopy. This method proposes a promising way for self-lubricating layer application in the steel matrix without complex operation and high economic cost.